9(x-2)+3x=6(2x+3)-8

Simple and best practice solution for 9(x-2)+3x=6(2x+3)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)+3x=6(2x+3)-8 equation:


Simplifying
9(x + -2) + 3x = 6(2x + 3) + -8

Reorder the terms:
9(-2 + x) + 3x = 6(2x + 3) + -8
(-2 * 9 + x * 9) + 3x = 6(2x + 3) + -8
(-18 + 9x) + 3x = 6(2x + 3) + -8

Combine like terms: 9x + 3x = 12x
-18 + 12x = 6(2x + 3) + -8

Reorder the terms:
-18 + 12x = 6(3 + 2x) + -8
-18 + 12x = (3 * 6 + 2x * 6) + -8
-18 + 12x = (18 + 12x) + -8

Reorder the terms:
-18 + 12x = 18 + -8 + 12x

Combine like terms: 18 + -8 = 10
-18 + 12x = 10 + 12x

Add '-12x' to each side of the equation.
-18 + 12x + -12x = 10 + 12x + -12x

Combine like terms: 12x + -12x = 0
-18 + 0 = 10 + 12x + -12x
-18 = 10 + 12x + -12x

Combine like terms: 12x + -12x = 0
-18 = 10 + 0
-18 = 10

Solving
-18 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 11m+4n-6m+7n= | | 4(5+3)=14 | | 5x-(x-8)=16 | | 12x-(4x-12)=7+7x | | 5+7x+3x=65 | | 7x+1=3x | | solvep-6=16 | | 8y-13y=20-25 | | slovep-6=16 | | 2(2d+1)=2/3 | | 6(1x+2)=2x | | x(9x+15)=14 | | x^4-3x^3-2=0 | | -5x+2-2x=-26 | | 2(x+1)=3(1+x) | | 7x+40=2x-11 | | y-11=-38 | | 7y-7-3y+6=0 | | 9x^4-6x^3+4x^2=0 | | -2y+6=7 | | ln(x)+ln(x+2)=ln(x+30) | | 34-4(2w+1)=10w-4(10+w) | | 0=-7x+6x+7 | | 150-11=x-5-13x | | 7/8+x=5/6 | | 4mn+1= | | 150-11=x-5-13p | | 8x-96=3x-6 | | 8x-(3x-8)=7+4x | | 3(x+2)+5=2-x | | 4(3x-11)=40 | | V=bwh |

Equations solver categories